Recent Progress in the Understanding of the Effect of Sympathetic Nerves on Hair Follicle Growth - Zhang, Jiarui; Chen, Ruosi; Wen, Lihong; Fan, Zhexiang; Guo, Yilong; Hu, Zhiqi; Miao, Yong (Frontiers in Cell and Developmental Biology, 2021)
Clinical observation and experimental studies have long suggested that the perifollicular nerves have nutritional and regulatory effects on the growth, development, and physiological cycle of hair follicles (HFs), even though the concrete mechanism remains obscure. Recently, with the progress of immunohistochemistry and molecular biology techniques, more innovation has been made in the study of the follicular sympathetic nerves and its nerve-effect factor norepinephrine affecting hair follicle stem cells. This review highlights the progress in the regulation of the sympathetic nervous system towards the growth of HFs.